SÃ”BRE A Escherichia coli, CONSIDERADA COMO ÃNDICE DE CONTAMINAÃ‡ÃƒO NAS ÃGUAS DE CONSUMO - Joly, S.; Marmo, J. C. (REVISTA DE AGRICULTURA, 2016)
SÃ”BRE A Escherichia coli, CONSIDERADA COMO ÃNDICE DE CONTAMINAÃ‡ÃƒO NAS ÃGUAS DE CONSUMO